First views on a community of oyster farmers in the municipality of Canguaretama/RN: an experience report (Research, Society and Development, 2023)
Our country's financial resources are aimed mainly at large producers, often leaving small enterprises on the margins of the market. The associations implemented in some regions of our country are an alternative to help these small entrepreneurs. One of the associations that stands out is the Association of Oyster Farmers of Canguaretama (AOCA), located in Canguaretama-RN, which offers support to oyster producers in the Porto community. This work aimed to carry out a diagnosis of oyster farmers linked to the Association, addressing socioeconomic aspects, the Association's role in the project, management of oyster cultivation and the community's traditional knowledge. Data were obtained through conversations with those responsible for the association and through the application of a questionnaire with all active producers. Through this methodology it was possible to obtain information and approach the oyster farmers, making it possible to know the local reality of the community. All project participants live in the Porto community, where they have their own homes, men and women participate in the association, performing the same functions in the work area, where they are leaving oyster extraction in the mangroves, and moving towards conscious production. As for schooling, participants ranged from illiterate to those with complete secondary education, with all producers participating in the project's beginning of professional training activities. The Association's work provided improvements for both parties involved, promoting the activity of oyster farming and promoting a better life for its members, as well as a process of social inclusion for the community involved in the project.